Liver and COVID-19 – Experience of a Regional Hospital - Fisher, David L; German, Anit; Mousa, Salman; Ghannam, Waleed; Malnick, Stephen (Archives of Clinical and Biomedical Research, 2021)
The pandemic caused by the novel coronavirus SARS-Co V-2 (COVID-19) has resulted in more than 5 million deaths worldwide and this number continues to rise. Liver enzyme abnormalities often occur in patients diagnosed with COVID-19 and it has been noted that the mortality rate is higher in patients with COVID-19 and severe acute liver injury (ALI) than without ALI. In our department, we treated 173 patients hospitalized with COVID-19 between March to August 2020, for whom follow-up data was available. In this paper we report on our observations of the association between COVID-19 and ALI. Data was collected from the ‘Ofek’ computer software. We found a statistically significant relationship between higher admission AST levels and severity of COVID-19 infection condition on admission (H= 7.139, P=0.028) which is consistent with previously reported studies. A higher proportion of patients had pre-existing liver disease (9%) than previously reported and we found a statistically significant relationship between under-lying liver disease and COVID-19 severity on discharge (P=0.039). Mortality for hospitalized patients with COVID-19 was 9.2%, which is less than the mortality previously reported. The significant association between AST levels and severity of COVID-19 infection highlights the need to test liver enzyme levels in all patients admitted with COVID-19.